Harmony in Difference: Inter-ethnic Harmony Model in a Pluralistic Community - Taufik (ANIMA Indonesian Psychological Journal, 2012)
The aim of this study was to identify factors of inter-ethnic harmony, shapes of the assimilation, and social interaction patterns of Javanese and Chinese in Sudiroprajan, Surakarta. Eight subjects were recruited, consisting of four Chinese and four Javanese. Verstehen technique was used to analyse the data. The result shows that: 1) factors of inter-ethnic harmony were social-economic equal, empathy, and inter-dependence attitudes; 2) shapes of assimilation were structural, cultural, and receptional; and 3) social interaction patterns of Javanese and Chinese consist of two kinds, namely the inside interaction of the kampung was harmony, but the outside inter- action of the kampung was potential to conflict. Penelitian ini bertujuan untuk mengidentifikasi faktor-faktor keharmonisan antaretnis, bentuk- bentuk asimilasi, dan pola-pola interaksi sosial antar etnis Jawa dan Tionghoa di Sudiroprajan, Surakarta. Subjek penelitian berjumlah delapan orang, terdiri atas empat orang etnis Tionghoa dan empat orang etnis Jawa. Analisis data menggunakan teknik Verstehen. Hasil penelitian menunjukkan: 1) Faktor-faktor kerukunan etnis Jawa dan Tionghoa antara lain: adanya persamaan status sosial ekonomi, empati, dan sikap saling-ketergantungan; 2) Bentuk-bentuk asimilasi meliputi asimilasi struktural, kultural, dan resepsional; dan 3) Pola-pola interaksi etnis Jawa dan Tionghoa terbagi menjadi dua yaitu interaksi di dalam kampung dan di luar kampung, interaksi di dalam kampung berjalan harmonis, sedangkan interaksi di luar kampung potensial konflik.